If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + 4) + 2x + -16 = 180 Reorder the terms: (4 + 6x) + 2x + -16 = 180 Remove parenthesis around (4 + 6x) 4 + 6x + 2x + -16 = 180 Reorder the terms: 4 + -16 + 6x + 2x = 180 Combine like terms: 4 + -16 = -12 -12 + 6x + 2x = 180 Combine like terms: 6x + 2x = 8x -12 + 8x = 180 Solving -12 + 8x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 8x = 180 + 12 Combine like terms: -12 + 12 = 0 0 + 8x = 180 + 12 8x = 180 + 12 Combine like terms: 180 + 12 = 192 8x = 192 Divide each side by '8'. x = 24 Simplifying x = 24
| (5x-2)(7-5x+2x)=0 | | 5+2d=29 | | 11j=6j-5 | | .17*1.2= | | 27=4x+7 | | (4s+5)(3s+8s-9)=0 | | 3c+4=11 | | 9x-5x^2=-2 | | 3+4=11 | | (x-2)(x+2x+4)=0 | | 9k-4=23 | | p+2=9 | | 3c+7=10 | | 2(m-3)(m-3)+2m^2+12m=-3m^2+5 | | 18+7x(32-16)= | | 4(d-9)+3(2d+8)=32 | | 6v-=42 | | 5=13-k | | (w+2)(w+2)-2(w+2)+9w=8 | | (5r-7s)(4r+3s)=0 | | .67(6h+3)=.33(3h-4)-h^2 | | (5r-7s)(4r+3s)=3 | | x^2+7x+49=0 | | 5w-3=12 | | 2b+3(3)=10 | | 4(d-5)+20=5-2d | | 2x=5y+13 | | (2a+3b)(5a-2b)=0 | | 8(2w-6)+4(-1-5w)=o | | (5y-3)(y+2)=0 | | 2.3=1.7+m | | 25=x^2+36 |